Two new species and three morphospecies of Ficophagus Davies & Bartholomaeus, 2015 (Nematoda: Aphelenchoididae) from Ficus subgenus Pharmacosycea (Moraceae) in Central America - Davies, Kerrie A (2017)
Aphelenchoidid nematodes were collected from the sycones of Ficus subgenus Pharmacosycea from Central America. Two new species of Ficophagus were recovered, and are described herein as F. maxima sp. n. and F. yoponensis sp. n. from Ficus maxima and F. yoponensis, respectively. They are differentiated from other species of the genus by a combination of morphological characters including having C-shaped females and spiral males, EP opening close to the lips, a short to long post-uterine sac, spicule characters, three pairs of subventral caudal papillae, DNA sequence data, biogeographical range, and host wasp and Ficus species affiliation. The new species are differentiated from each other by spicule characters, length of the post-uterine sac, spermatheca shape, and female tail shape. In addition, three morphospecies were collected from sycones of Ficus glabrata, F. insipida and F. tonduzii, respectively. Their morphological descriptions are presented but these taxa are not formally named as they currently lack molecular data.